Replication Data for: Towards an assessment of on-farm niches for improved forages in Sud-Kivu, DR Congo - Paul, Birthe K.; Muhimuzi-Lwaboshi, Fabrice; Bacigale, Samy B.; Wimba, Benjamin M.M.; Chiuri, Wanjiku L.; Amzati, Gaston S.; Maass, Brigitte L. (International Center for Tropical Agriculture, 2017)
Inadequate quantity and quality of livestock feed is a persistent constraint to productivity for mixed crop-livestock farming in eastern Democratic Republic of Congo. To assess on-farm niches of improved forages, demonstration trials and participatory on-farm research were conducted in four different sites. Forage legumes included Canavalia brasiliensis (CIAT 17009), Stylosanthes guianensis (CIAT 11995) and Desmodium uncinatum (cv. Silverleaf), while grasses were Guatemala grass (Tripsacum andersonii), Napier grass (Pennisetum purpureum) French Cameroon, and a local Napier line. Within the first six months, forage legumes adapted differently to the four sites with little differences among varieties, while forage grasses displayed higher variability in biomass production among varieties than among sites. Farmers’ ranking largely corresponded to herbage yield from the first cut, preferring Canavalia, Silverleaf desmodium and Napier French Cameroon. Choice of forages and integration into farming systems depended on land availability, soil erosion prevalence and livestock husbandry system. In erosion prone sites, 55–60%of farmers planted grasses on field edges and 16–30% as hedgerows for erosion control. 43% of farmers grew forages as intercrop with food crops such as maize and cassava, pointing to land scarcity. Only in the site with lower land pressure, 71% of farmers grew legumes as pure stand. When land tenure was not secured and livestock freely roaming, 75% of farmers preferred to grow annual forage legumes instead of perennial grasses. Future research should develop robust decision support for spatial and temporal integration of forage technologies into diverse smallholder cropping systems and agro-ecologies.